Monitoring and Predicting Changes in Reference Evapotranspiration in the Moghan Plain According to CMIP6 of IPCC - Yagob Dinpashoh; Pouya Allahverdipour (محیط زیست و مهندسی آب)
Estimating the optimal water requirement requires determining the relationship between climatic conditions and evapotranspiration. As a result, water resource management relies on accurate estimation of evapotranspiration. This study aimed to monitor and predict the reference evapotranspiration, ET0, in the Moghan Plain, considering the impact of climate change. ET0 was calculated by the PMF56 method using CROPWAT software. The 30-year data (1993-2022) of the Parsabad synoptic station and the output of CMIP6, including the HadGEM3-GC31-LL model and the SSP1-2.6, SSP2-4.5, and SSP5-8.5 scenarios were used. The results showed that the precipitation, minimum temperature and maximum temperature in the Moghan Plain from 261 mm, 9.95 °C and 21.21 °C in the base period, respectively, will reach 361 mm, 16.04 °C and 27.68 °C at the end of the century. Under the effects of climate change, ET0 will increase in the future. The severity of the climate change impact on ET0 in the Moghan Plain is greater in the warm months, and the greatest increase will be under the SSP5-8.5 scenario. The ET0 in Moghan Plain reached 1114 mm/yr in the base period, with an increase of 20% to 1334 mm/yr at the end of the century. Considering the greater share of Iran's water consumption in the agricultural sector, especially in areas such as the Moghan Plain, ET0 changes should be considered in engineering and water resource management programs.